The riddle of Cantinflas essays on Hispanic popular culture - Stavans, Ilan (University of New Mexico Press, 2012)
"A collection of essays on kitsch and high art in the Americas makes a return with thirteen new colorful conversations that deliver Stavans's trademark wit and provocative analysis. The collection has the power to go beyond common assumptions and helps us understand Mexican popular culture and its counterparts in the United States"--Provided by publisher.